Analisis Faktor Determinan Kompetensi Kepala Ruang Perawatan - Erly Frida Hasugian, Elisabeth; Tarigan, Emiliana (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2024)
Problems related to the leadership ability of the Head of the Room in the health service environment which can affect the implementation of his duties and the performance of the team under him, such as accompanying the implementing nurse in carrying out nursing care, are considered not optimal, which can have an impact on the quality of nursing services provided. The ability of the Head of the Room to evaluate the performance of implementing nurses has also not been carried out optimally, which can affect the development and improvement of the performance of the staff under him. From here, there are challenges in leadership abilities, mentoring, and performance evaluation that need to be addressed to increase management effectiveness and efficiency in the health service environment. This emphasizes the importance of developing leadership and managerial skills for heads of treatment rooms. Aim of the research to gain an in-depth understanding of the qualifications, skills and leadership traits required by a Head of Care and be able to identify trends, best practices and current findings related to leadership competencies in the care environment. This research uses a literature review method by searching databases via Semantic Scholar and Google Scholar and also carrying out PICOT analysis of the article. Journal search results from this database are selected based on keywords, articles and year of publication of the journal. Journal searches used the keywords Competence, Head Nurse and Determinant Factors. The screening results of journals published in the last 5 years found that 30 full text journals were assessed for eligibility. After conducting feasibility studies, 20 journals were found that were in accordance with the research objectives, of which 1 journal was discarded because it was the same and 2 journals were excluded because they were not published and were not full text, resulting in 17 full text journals being reviewed. The results of this study indicate that the leadership education program for the head of the nursing room has a significant positive influence on the level of motivation and empowerment of the head nurse, and the emotional intelligence of the head nurse has a positive correlation with the work involvement of nursing staff to improve ability and performance in providing professional nursing care. Investment in education and competency development of ward heads is very important to improve nurse performance and provide quality and safe nursing care